Research in organizational change and development. - Shani, Abraham B.; Noumair, Debra Ann (Research in organizational change and development ;, 2015)
Research in organizational change and development (ROCD) brings forth the latest scholarly work and practice in the fields of organization development and organizational change. The objectives are to highlight the latest advances in thought, ideally supported by research and practice. The series is a resource for scholars who are interested in well-integrated reviews of the literature, advances in research methods, and ideas about practice that open new ways of working with organizations to create more successful and sustainable approaches to change.